A Contribuição da Altura Para a Impressão Espacial no Contexto da Produção Áudio - Joana Alexandra de Castro e Rodrigues (2019)
This dissertation is proposed in a context of renewed interest in sound spatialization and in the understanding of how it can be used in the context of musical production for multichannel reproduction formats. Developed in partnership with Orquestra Jazz de Matosinhos, the present study explores different strategies, systems and technologies of audio production in order to understand how the addition of height reproduction channels improves the spatial impression of the listener. To better understand these concepts, a paired comparison evaluation was made between reproduction setups - with and without the height layer - through the subjective assessment of two different recording techniques applied to these systems. In this way, this study intends to explore and report not only musical production strategies but also to analyze the subjective response to the acoustic stimuli, focusing on the spatial impression and its contribution to musical appreciation.